2017
DOI: 10.1039/c7ra08645h
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic fabrication of hollow protein microcapsules for rate-controlled release

Abstract: Droplet-based microfluidics is an emerging technique that is capable of producing sophisticated supramolecular microcapsules in one step. However, food materials, due to their physical and chemical complexity, have limited success with microfluidic processes. The objectives of this work were to produce food-grade protein microcapsules in a microfluidic system and to control their structural properties by adjusting the formulation and flow rates. In this study, a T-junction microfluidic chip was used to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Such changes will have an effect on the study of single variables. Moreover, the addition of surfactants may be strictly limited sometimes, especially in certain medical 25 or biological 26,27 applications.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes will have an effect on the study of single variables. Moreover, the addition of surfactants may be strictly limited sometimes, especially in certain medical 25 or biological 26,27 applications.…”
Section: Introductionmentioning
confidence: 99%
“…The thicker layer could potentially provide better protection of the core material in the oil phase. A similar strategy has been implemented in previous work to improve nutrient retention or to extend release duration by forming thick wall materials . It was also found that the surface tension of both UP1 and UP4 was lower than that of OP (supporting information, Table S1), indicating that an improvement in the surface activity of pectin was achieved through the ultrasonic treatment.…”
Section: Resultsmentioning
confidence: 59%
“…The CD spectra were collected using JASCO J-715 spectropolarimeter (Jasco Inc., Easton, MD) and the method in a previous publication was used with some modifications ( Feng and Lee, 2017 ). The 100 times diluted samples were placed in an 1 cm path length quartz cell, and the wavelength ranged from 200 to 250 nm at 25 °C with the scanning speed of 50 nm/min.…”
Section: Methodsmentioning
confidence: 99%